Cybersecurity Threats in Syria and Its Implications for International Relations (Latakia University Journal - Economic and Legal Sciences Series, 2025)
Cybersecurity is a vital field that focuses on protecting electronic systems and data from cyber attacks and threats. This field includes the application of a set of procedures and techniques that aim to protect data and ensure the confidentiality and integrity of information. Awareness and training for users are an essential part of cybersecurity strategies, as they contribute to enhancing the level of awareness of potential risks and available protection methods. Common threats in this field include ransomware attacks, database hacking, and malware. Technologies used in information security, such as encryption and intrusion detection systems, contribute to building a comprehensive protection system against these threats. This study addresses the concept of cybersecurity, its objectives, and its importance, in addition to the main strategies that can be adopted in this field. The most prominent findings reached by the researcher are:1- Increase awareness and training: The need to enhance training and awareness programs for IT workers and ordinary users about the importance of cybersecurity and available means of protection.2- Periodic risk assessment: The importance of conducting periodic risk assessments to identify gaps and update protection strategies in line with current threats.3- Developing national strategies: Countries must seek to develop comprehensive national strategies for cybersecurity that include all vital sectors. These results emphasize the importance of cybersecurity as a fundamental element in protecting information and enhancing digital security in the modern era.
Keywords: Cybersecurity, Cybersecurity Threats